2008
DOI: 10.1158/1055-9965.epi-08-0413
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Alpha Extended Haplotypes and Risk of Gastric Carcinoma

Abstract: The tumor necrosis factor A (TNFA)-308*A allele has been found to confer an increased risk of gastric carcinoma. Inconsistency in risk estimates across populations lead us to hypothesize about the presence of an alternative causal locus in the same chromosomal region. A suitable approach is to determine the tumor necrosis factor haplotypic structure in order to clarify whether the association between the *A allele and the increased risk of gastric carcinoma is etiologic or secondary to linkage disequilibrium. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 31 publications
(32 reference statements)
0
18
0
Order By: Relevance
“…None of the polymorphisms identified in the promoter of the TGF-b1 gene in this study corresponded to the homologous position of the TGF-b1 -509 C[T variant identified in humans. A polymorphism identified in the promoter of the human IFN-cR1 gene was found to be associated with increased risk of developing early gastric carcinoma (Canedo et al 2008), and in vitro, this polymorphism (-56T[C) has been shown to alter promoter activity (Rosenzweig et al 2004). Later, in silico analysis predicted an AP-2/AP-4 consensus binding site around position -56 of this gene in humans, explaining the observed effect on promoter activity.…”
Section: Discussionmentioning
confidence: 99%
“…None of the polymorphisms identified in the promoter of the TGF-b1 gene in this study corresponded to the homologous position of the TGF-b1 -509 C[T variant identified in humans. A polymorphism identified in the promoter of the human IFN-cR1 gene was found to be associated with increased risk of developing early gastric carcinoma (Canedo et al 2008), and in vitro, this polymorphism (-56T[C) has been shown to alter promoter activity (Rosenzweig et al 2004). Later, in silico analysis predicted an AP-2/AP-4 consensus binding site around position -56 of this gene in humans, explaining the observed effect on promoter activity.…”
Section: Discussionmentioning
confidence: 99%
“…An association of TNF-α -308G>A (rs1800629) with susceptibility/resistance to GC development has been widely investigated and yielded conflicting results. Studies including GC patients and controls from China (7)(8)(9)(10)(11)(12)(13)(14), Brazil (15,16), Portugal (17,18), United States (19), Poland (20), South Korea (21-23), Honduras (24), Italy (25), Colombia (26), and Japan (27) have been associated with susceptibility to GC development. However, other studies including those from India (28), Brazilian (29,30), Romania (31), Spain (32,33), South Korea (34,35), China (36), Mexico (37), Germany (38) and Finland (39) failed to show a possible link between the TNF-α (-308G>A) polymorphism and GC.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, several environmental factors, including diet, tobacco smoking and Helicobacter pylori infection, have been shown to be responsible for gastric carcinogenesis (2,3). Besides environmental factors, genetic factors also play an important role in the development of GC, and this is confirmed by the fact that only a small proportion of individuals exposed to known environmental risk factors develop GC (4,5). Additionally, recent studies have shown that single-nucleotide polymorphisms (SNPs) in genes encoding tumor necrosis factor α, COX-2, and CD14 are associated with increased GC risk (5-7), indicating that genetic variation contributes to GC carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%